THE PROBLEM OF SECXUAL SOCIALIZATION OF PUPILS IN THE NATIONAL PEDAGOGICS OF THE 20TH CENTURY - Volodymyr Kravets (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2017)
In the article the analysis of the national sexual pedagogics formation is done, the difficulties of understanding the term "sexual pedagogics" are shown; sexual pedagogical discourse of the 20th century is generalized. The ideas of the main trends of sexual socialization of the 1920-30's are analyzed; the causes which restrained sexual pedagogics development in 1970-80's are pointed out. In the article the different trends of sexual socialization development are presented, in particular a gender education, sexual education and sexual culture formation. The main problems of national sexual-pedagogical discourse are pointed out: the age in which the gender education and sexual awareness should start was grounded and also the main sources of social socialization were defined, its content and process were analyzed. The main concepts of sexual socialization were analyzed. The main stress was made on the influence of total ideologization of soviet society on sexual socialization of the school youth. The contribution of the prominent pedagogues P. Blonskyi, A. Makarenko, V. Suhomlynskyi and others into the development of the national sexual pedagogics was analyzed. The unsuccessful attempts to implement the course of "Ethics and Pedagogics of Sexual Life" into a soviet school were shown. The perspectives of the development of sexual pedagogics in independent Ukraine were sketched.